Some surface properties of thermally modified scots pine after artificial weathering - Baysal, Ergun; Degirmentepe, Selim; Simsek, Hakan (Maderas. Ciencia y Tecnología, 2025)
In this study, it was aimed to investigate some surface characteristics such as surface roughness, color, and glossiness of Scots pine (Pinus sylvestris) wood specimens after 500 hours artificial weathering exposure. The results showed that surface characteristics of thermally modified Scots pine gave better results than unmodified Scots pine after artificial weathering. Artificial weathering caused an increase in surface roughness and a decrease in glossiness of Scots pine wood. Results showed artificial weathered wood become darker, reddish, and yellowish. Generally, higher duration and temperature for Scots pine resulted in better surface characteristics of Scots pine after artificial weathering.